Efficient Unnatural Protein Production by Pyrrolysyl-tRNA Synthetase With Genetically Fused Solubility Tags - Koch, Nikolaj G.; Baumann, Tobias; Budisa, Nediljko (Frontiers in Bioengineering and Biotechnology, 2021)
Introducing non-canonical amino acids (ncAAs) by engineered orthogonal pairs of aminoacyl-tRNA synthetases and tRNAs has proven to be a highly useful tool for the expansion of the genetic code. Pyrrolysyl-tRNA synthetase (PylRS) from methanogenic archaeal and bacterial species is particularly attractive due to its natural orthogonal reactivity in bacterial and eukaryotic cells. However, the scope of such a reprogrammed translation is often limited, due to low yields of chemically modified target protein. This can be the result of substrate specificity engineering, which decreases the aminoacyl-tRNA synthetase stability and reduces the abundance of active enzyme. We show that the solubility and folding of these engineered enzymes can become a bottleneck for the production of ncAA-containing proteins in vivo. Solubility tags derived from various species provide a strategy to remedy this issue. We find the N terminal fusion of the small metal binding protein from Nitrosomonas europaea to the PylRS sequence to improve enzyme solubility and to boost orthogonal translation efficiency. Our strategy enhances the production of site-specifically labelled proteins with a variety of engineered PylRS variants by 200-540 %, and further allows triple labeling. Even the wild-type enzyme gains up to 245 % efficiency for established ncAA substrates.